Main Soil Nutrient Characteristics of Cultivated Land in Surface Tension Fracture Area of Huaibei Mining Area - Tingyu Fan; Yingxiang Chen; Akang Lu; Zhaoyao Yan; Yifan Zhao; Jiaping Yan; Shun Wang; Xingming Wang; Xiangping Wei; Yanhai Zhang (Shuitu baochi tongbao, 2023)
[Objective] The influences of surface tension fractures caused by coal mining subsidence on the soil quality of cultivated land were analyzed, and the changes in soil nutrients before and after coal mining subsidence were quantified, in order to provide a theoretical basis for the pre-mining and in-mining management of land in the subsidence area. [Methods] The study was conducted in the surface tension fracture area of the Suntuan Mine in the Huaibei mining area. Samples were collected before subsidence (April 2019), and after sibsidence (December 2019, July 2020). Five sampling points were randomly located before subsidence. Two typical longitudinal tension fractures were selected after subsidence, and the subsidence area was divided into three zones from the top to the bottom of the subsidence slope. Thirteen sampling points were located on both sides of each fracture. At each sampling point, one soil sample was collected every 20 cm of soil depth. Sample collection was completed in December 2019 and July 2020. Six soil indicators were monitored: water content, organic matter, fast-acting potassium, fast-acting phosphorus, total nitrogen, and total phosphorus. [Results] There were significant differences in soil moisture content, organic matter, available potassium, and total phosphorus between the two samplings in the tension fracture area (p<0.01), but there were no significant differences in available phosphorus and total nitrogen (p>0.05). Principal component analysis showed that the first principal components were organic matter, total nitrogen, and total phosphorus (positive), and the second principal components were water content and fast-acting potassium (negative). Based on the comprehensive nutrient evaluation-principal component score analysis, the integrated nutrient score increased with time. However, the nutrients in the tension fracture zone gradually increased from the top to the bottom of the subsidence slope. [Conclusion] Surface tension fractures were widely distributed in the coal mining subsidence area, leading to a decline in soil quality.